Hardware and software implementation of POCT1-A for integration of point of care testing in research - Nathan T.P. Patel; Magan R. Lane; Timothy K. Williams; Lucas P. Neff (Elsevier, 2022)
Point of care testing (POCT) is increasingly utilized in clinical medicine. Small, portable testing devices can now deliver reliable and accurate diagnostic results during a patient encounter. With these increases in POCT, the issue of data and results management quickly emerges. Results need to be cataloged accurately and efficiently while the providers/support staff are simultaneously managing patient encounters. The integration of electronic medical records (EMR) as data repositories requires that point of care testing data imports automatically into the EMR. POCT1-A was developed as a standard communication language for POCT device manufacturers to streamline automatic data import integration. While all modern POCT devices are built with this connectivity, the systems that provide the integration layer are often proprietary and require a fee for service. In the research environment, there is not enough throughput to justify the practical investment in these data management architectures. Moreover, researcher needs are different and unique compared to data management systems for clinicians. To meet this need, we developed a novel hardware and software connectivity solution using commercially available components to automate data management from a point-of-care blood biochemical analyzer during a critical care study in the preclinical research environment.